PERAN KH. ABDULLAH ABBAS DALAM PERKEMBANGAN PONDOK BUNTET PESANTREN SERTA PENGARUHNYA SEBAGAI KIAI KHOS DI INDONESIA - Jihan Amalia Hasanah (IAIN Syekh Nurjati Cirebon, 2017)
AbstractKH. Abdullah Abbas is a Kiai Khos who became the reference of Muslims in Indonesia. It also has many services to this nation. In addition to being the Chief of Staff of the Hizbullah Battalion during the colonial period, he was active in NU activities and struggles. This research becomes more interesting, because KH. Abdullah Abbas has also made Pondok Pesantren Buntet growing and increasingly known by the Indonesian society. In addition to his excess, also because KH. Abdullah Abbas seeks to improve the quality and quantity of education by combining the salaf and the kholaf study system in Buntet Pesantren. On that basis, researcher was interested to reveal more deeply related to the role of KH. Abdullah Abbas in developing Pondok Pesantren Buntet and its influence as Kiai Khos in Indonesia. Keywords: Pesantren, Pesantren Buntet, KH. Abdullah Abbas, Kiai Khos, Hizbullah.